Power Sector and Hydropower Development in Nepal - Shrestha, Rabindra Bahadur (Hydro Nepal: Journal of Water, Energy and Environment, 2015)
This paper is prepared on the answer to the valuable comments made by late Jeewan P. Thanju on my article ‘Water Resources of Nepal: Misconception and Reality’ published in The Rising Nepal on January 23 & 24, 2014.The rivers of Nepal possess sufficient hydropower potentiality to enhance the country’s socio-economic development. However, some spurious expert and vested interest group exaggerated the hydro potentiality and distorted the fact of water resources development prospective in Nepal. This has created confusion among the policymakers, politician and multilateral agencies. As a result, hydropower development in Nepal has headed for wrong course, and now the power sector, the vital impetus for socio-economic development is in dire strait. This paper highlights the uniqueness and distinct technical features of Nepalese Power Sector. In this paper important component like Integrated National Power System/Grid (INPS), Power Generation Modality (Hydropower, Thermal/Nuclear Plants and Diesel Plants) are well described and Master Plan, Project Selection, Construction Schedules and Hydropower potentiality of Nepal are discussed in detail. In a severe power and energy crisis situation in the country, power export is not recommended. Nepal needs 3000 MW to reach the level of other south Asian nations. INPS is owned and operated by NEA; therefore NEA also has the responsibility to prepare master plan for power generation, transmission and distribution. But, the Department Electricity Development a regulatory body of Ministry of Energy of is undertaking / carrying out feasibility study without taking care of INPS/country’s power requirement. This has created duplication of work and confusion; as such the Ministry of Energy deviated from its responsibility of preparing sound policy, regulation and monitoring them strictly. The Ministry shouldn’t indulge in feasibility study, construction and operational activities, which come under the responsibility of concerned technical department /authority. DOI: http://dx.doi.org/10.3126/hn.v16i0.12214 HYDRO Nepal Journal of Water Energy and Environment Issue. 16, 2015, January Page: 18-22 Upload date: March 1, 2015